High-resolution esophageal manometry. Initial experience in a department of general surgery - Chinelli, Javier; Rodríguez, Gustavo (Revista Argentina de Cirugía, 2026)
Background: Manometry is considered the gold standard for the diagnosis of motility disorders of the esophagus. There are currently no national reports documenting the use and results of high-resolution manometry (HRM). Objective: The aim of this study is to describe the technique and the results of the initial use of HRM in patients with gastroesophageal disorders. Material and methods: We conducted an observational and retrospective study using the clinical records of patients referred for HRM for assessment of gastroesophageal disorders between June 2019 and June 2014. Motility disorders were defined according to the Chicago classification v3.0. Results: The clinical records of 89 patients were analyzed. The reasons for evaluation were gastroesophageal reflux (GER), preoperative assessment of bariatric surgery and revision surgery, functional dysphagia, failed Heller myotomy and non-cardiac chest pain. All the patients had previously undergone an endoscopic evaluation. The following parameters were evaluated in each case: morphology of the esophagogastic junction (EGJ), deglutitive EGJ relaxation, propagation of the peristaltic wave, contractile vigor of the esophageal body, peristaltic integrity and pressurization pattern. Most motility disorders occurred in the GER group. Conclusion: High-resolution esophageal manometry provided relevant information for the diagnosis and treatment of diverse gastroesophageal disorders.